Harnessing Local Potential in Dusun Bengkung for STEAM Education: A Case Study Of Literacy Advancement at TBM Pelopor Literasi Dusunku - Jannana, Nora Saiva; Danuri, Danuri; Wardani, Ajeng Kusuma (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
This study explores the potential of Dusun Bengkung's local resources to develop Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based educational activities aimed at enhancing literacy and creativity among school-aged children. Employing a qualitative case study methodology, data were gathered through focus group discussions (FGDs) involving 15 community stakeholders and document analysis. The findings reveal three key local potentials: (1) strong social collaboration rooted in the village's cultural traditions, (2) abundant natural resources such as bamboo, rice, and fishponds, and (3) a substantial demographic of school-aged children eager for creative engagement. STEAM activities tailored to these local resources included bamboo-based string art, water filtration techniques, and natural dyeing using local plants. The Taman Bacaan Masyarakat (Community Reading Center) Pelopor Literasi Dusunku and its associated Rumah Belajar (Learning House) served as central hubs for facilitating these activities, supported by thematic community service programs and literacy initiatives aligned with the National Literacy Movement. The study highlights the impact of integrating local wisdom into STEAM education to foster literacy, creativity, and cultural sustainability. However, its focus on a single rural community limits generalizability. Future research should investigate the scalability of such models across diverse cultural and ecological contexts. Additionally, integrating digital tools into these localized frameworks offers opportunities for advancing digital literacy in rural education.